A COMPARATIVE STUDY BETWEEN ENGLISH AND SPANISH GRAMMAR - Nur, Muhammad (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
This research is a descriptive one that tries to find the differences and similarities between English and Spanish grammar. The data of this research are the English and Spanish grammar. The sources of the data are English and Spanish printed texts in the form of books, magazines, newspapers, etc. The data are collected by using jotting down technique. Then, the data are analyzed by using the model suggested by Mile and Huberman. The model is called interactive model. This model has three steps. They are as follows: (1) data reduction, (2) data display, and (3) conclusion drawing.